2021
DOI: 10.1111/icad.12512
|View full text |Cite
|
Sign up to set email alerts
|

Responses of ground beetle (Coleoptera: Carabidae) assemblages to stand characteristics and landscape structure in riparian poplar forests

Abstract: 1. Many carabid beetles are among the most important biocontrol agents and are biological indicators of environmental change, although relatively little is known about how local and landscape factors affect forest ground beetle assemblages. Understanding such effects of multi-scale environmental drivers on ground beetles can promote carabid diversity and conservation.2. Ground beetles were sampled by pitfall trapping in 40 poplar forest stands (sampling plots) along the Irtysh River in Northwestern China. We i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 84 publications
1
7
0
Order By: Relevance
“…These positive changes appear to have been further exacerbated by decreasing tree density, as carabid abundance increased in these mixed forests when the total number of trees per plot was reduced from 100 to 66 and 40. This positive effect of reduced forest density on carabid abundance is consistent with previous studies (Ings & Hartley, 1999;Lange et al, 2014;Wang et al, 2021;Yi & Moldenke, 2005), showing that that greater canopy openness could promote more abundant or diverse understory vegetation, providing more hunting and foraging niches and protection from predators and desiccation. This would also explain why the reduction in tree density had no effect in pure stands of maritime pine (Pp100 vs. Pp50), which shaded the understory vegetation even at the reduced density.…”
Section: Effects Of Tree Species Mixing On the Carabid Communitysupporting
confidence: 91%
See 1 more Smart Citation
“…These positive changes appear to have been further exacerbated by decreasing tree density, as carabid abundance increased in these mixed forests when the total number of trees per plot was reduced from 100 to 66 and 40. This positive effect of reduced forest density on carabid abundance is consistent with previous studies (Ings & Hartley, 1999;Lange et al, 2014;Wang et al, 2021;Yi & Moldenke, 2005), showing that that greater canopy openness could promote more abundant or diverse understory vegetation, providing more hunting and foraging niches and protection from predators and desiccation. This would also explain why the reduction in tree density had no effect in pure stands of maritime pine (Pp100 vs. Pp50), which shaded the understory vegetation even at the reduced density.…”
Section: Effects Of Tree Species Mixing On the Carabid Communitysupporting
confidence: 91%
“…This effect of canopy cover on the abiotic conditions of the understorey is known to favour forest‐dwelling carabid beetles, while it disadvantages open‐habitats species that prefer drier conditions (Ings & Hartley, 1999; Negro et al, 2014). This generally results in an overall decrease in species richness and functional diversity of carabid beetles as tree density or canopy closure increases (Lange et al, 2014; Niemelä et al, 1996) due to the loss of these open‐habitat species (Spake et al, 2016; Wang et al, 2021). However, daily temperature and amplitudes of vapour pressure deficit also decrease with increasing stand structural complexity (Ehbrecht et al, 2017), which has been shown to be greater in mixed species forests.…”
Section: Introductionmentioning
confidence: 99%
“…Landscape land use changes and vegetation management influence the functional dispersion of riparian ground beetle communities. The highest value of this component was found in landscapes with medium vegetation productivity [111]. The only study of riparian spider FD found functional evenness to be the most sensitive metric to environmental changes, slightly increasing with urbanization.…”
Section: Functional Diveristy Componentsmentioning
confidence: 95%
“…Functional dispersion is the most used FD component for the research of riparian predatory arthropods. It has been studied in response to the following: flooding [17,24], riparian bank type (i.e., cut-off or slip-off banks) [25], riparian vegetation characteristics (i.e., natural or managed vegetation; % of vegetation cover) [25,111], and land use change (i.e., landscape vegetation productivity index) [111]. Carabid functional dispersion, used to evaluate functional redundancy, was lower in flooded habitats [17,24], demonstrating the increased flood resilience of local communities.…”
Section: Functional Diveristy Componentsmentioning
confidence: 99%
See 1 more Smart Citation